PERBAIKAN ALGORITMA STEGANOGRAFI TEKNIK LEAST SIGNIFICANT BITS UNTUK APLIKASI KEAMANAN DATA - Tika Erna Putri; Muhammad Rifqi Al Fauzan; Prima Asmara Sejati (Prodi Fisika FST UNJA, 2017)
Security issues have become major problem in the field of data communications, specifically in the data transmission through the internet. One of the solutions is to hide the messages through a digital media so the attention of the attacker or third party can be avoided, this method is known as steganography. In this research, we use images as digital media. We modify the Least Significant Bit (LSB) which is the most commonly used technique in steganography. Unfortunately LSB has poor security level since it is already widely known technique. Therefore, it is important to modify the algorithm of LSB to ensure its security aspect. An improvement to LSB technique is suggested by selecting only odd pixels and ignoring even pixels in the implementation of steganography. We successfully implement the modified LSB algorithm by using RBG image and grayscale image as steganography media. Mean Squared Error (MSE) and Peak Signal-to-noise Ratio (PSNR) are employed to evaluate the stego-image quality. Our calculations show that the modified LSB algorithm provides better results than the conventional LSB. The conventional LSB algorithm gives 1.98 10-5 for MSE and 95.20893 dB for PSNR calculations, while the modified LSB gives 1. 80 10-5 and 95.6101 dB for MSE and PSNR, respectively.